I'tikaf Therapy as an Effort to Prevent Terrorism: A Study of Al-Qurtubi's Interpretation of QS. Al-Baqarah: 187 - Basid, Abdul (AL QUDS : Jurnal Studi Alquran dan Hadis, 2022)
This study wants to find out what role I'tikaf plays in stopping radical ideas and acts of terrorism (counterterrorism). The research method used in this paper is qualitative, and the type of research is literature research. The main reference is the interpretation of al-Qurthubi and a few journals and books that are related to the topic. The study started by trying to figure out how Q.S. Al-Baqarah verse 187, which talks about I'tikaf from the point of view of al-Qurtubi and is in the book al-Jami' li Ahkaam al-Quran, should be interpreted. It then looked for links between I'tikaf therapy and preventing terrorism. This study looked for different ways to fight terrorism in the fields of psychology and Sufism. The research shows that I'tikaf is a way to get closer to Allah and a form of psychosis therapy for the four dimensions of the mind. It is also thought to help stop people from doing terrorist acts. By putting I'tikaf into practice with a clean heart, psychic and Sufistic people, including terrorists, will be able to see what is right and what is wrong